PENGARUH KEDISIPLINAN SALAT DAN PEMBIASAAN PUASA SUNAH TERHADAP AKHLAK PESERTA DIDIK DI MTS AL-MUBAARAK KOTA BENGKULU - Nyimas Hartini (Al-Bahtsu: Jurnal Penelitian Pendidikan Islam, 2017)
This study aims to determine the effect of habituation discipline of prayer and fasting sunna against the morals of students in MTs Mubaarak Bengkulu City. In the study researchers used three variables: the discipline of prayer (the independent variable X1), habituation fasting Sunna (independent variable X2) and character of students (dependent variable Y). This research is quantitative associative conducted by collecting data in the form of figures kemudin processed and analyzed. The data collection technique is by distributing a questionnaire with answer options that are available. As for the number of items a matter of 25 to the variable (Y), 25 for the variable (X1), and 15 for the variable (X2). The population in this study were 101 students and sampled as many as 30 students. Data analysis technique used was to test the assumption of linear regression. The results of the data analysis At the significance level α = 5%, indicating that the discipline of prayer and fasting sunna habituation to the morals of learners very significant effect. This is seen in the F test value F_hitung> F_ tabel (5.393> 1.89), so it can be said that the X1 and X2 affect the Y. This means that if the discipline of prayer and fasting sunna enhanced habituation it will affect the character of students in MTs Al mubaarak city of Bengkulu.